Ilonoesi: Is the Subject a Part or Limit of the World? - Barison, Marcello (Scenari, 2022)
Reasoning around the proposition 5.632 of the Tractatus, the contribution focuses on the relationship between subject and world, questioning if the two terms can be conceived as entirely separate, if instead they are continuous instances that have at least a contact surface, therefore a shared positional field, or if they are integrated within the same dimension, implying thus a mutual immanence. The analysis is divided into three different sections. The first one (Iletics of the Noumenon) focuses on the noumenal nature of matter itself, conceived in the light of Kant’s reference to a “transcendental object” and correlating it to the concept of plain as it is elaborated in Gerald Murnane’s most celebrated novel. The second one (Noetics of the Noumenon) focuses instead on the noumenal nature of the subjective foundation of thought, referring mainly to the Wittgensteinian approach developed in the Tractatus. The third, which intends to formulate theoretically the point of arrival of the entire contribution – reached by leveraging some important Machian considerations dealing with the relationship between the forms, mutually open, of subject and object – outlines the concept of Ilonoesis as a joint dimension, transcendental and material together, proper to their ontological indiscernibility.